Determinan Tingkat Partisipasi Angkatan Kerja Perempuan di Provinsi Jawa Barat - Windu Kholbiya Sajati; Amin Pujiati (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
Labor is an important factor in supporting the success of development. The success of a development in human resources can be seen from the increasing role of women in employment. The female labor force participation rate (TPAK) shows how actively women participate in the labor force. So the purpose of this study is to analyze the factors that influence the Female Labor Force Participation Rate (TPAK) in West Java during the 2019-2023 period. The variables studied include Gender Empowerment Index (IDG), Regional Minimum Wage (UMR), Female Average Years of Schooling (RLS), and Female Life Expectancy (AHH). The method used is panel data regression with the Fixed Effect Model (FEM) as the selected model. The results show that IDG and UMR have a positive but insignificant effect on female TPAK in West Java, while female RLS has a negative and significant effect. In contrast, female AHH has a positive and significant effect on female TPAK in West Java. This finding shows that despite the increase in gender empowerment, women in West Java still work more in the informal sector. In addition, an increase in the minimum wage does not directly encourage an increase in women's TPAK, while education and health play an important role in increasing their participation in the labor market. Therefore, more effective policies are needed to improve access to education, health, and employment opportunities for women in West Java.